Copy Number Status of TERT Gene in a Myeloid Leukaemia Cell Line, K562: Application of Interphase Fluorescence in situ Hybridization (FISH) Analysis - Othman, Ahmad Syibli; Mohd Adam, Nor Atifah; Ankathil, Ravindran; Hassan, Rosline (2011)
Telomerase is ribonucleoprotein enzyme complex consisting of two main core components; reverse transcriptase (TERT), and RNA template for telomeric DNA synthesis (TERC). TERT gene acts as catalytic component in this enzyme and is located on chromosome 5p15. It has been reported that there is an amplification or increase of TERT gene copy number in human cancer cell lines and primary tumour samples which may associate with increased telomerase activity. In our study, dual-color assay probe was used in fluorescence in situ hybridization (FISH) analysis that covered the genomic region encoding TERT (Red signal) together with a specific sequence of EGR1 (Green signal) at 5q31 to facilitate chromosome identification. In normal cells, the FISH signal pattern was observed as two green signals and two red signals (2G2R). Amplification of the TERT gene has been detected in more than 90% of the cells in cell line in the leukaemia. Besides that, aneusomy of chromosome 5 was also detected indicating the presence of three copies of chromosome 5 with 3G3R signal pattern. Thus, the application of interphase FISH technique for detection of TERT gene amplification has been successfully optimized.